Pengaruh Sarana Pembelajaran dan Motivasi Belajar Matematika Terhadap Kemandirian Belajar Peserta Didik Kelas VII SMP Negeri 2 Kotabaru - Hartini Hartini; Danial Danial; Munawaroh Munawaroh (Universitas Islam Ahmad Dahlan (UIAD) Sinjai, 2021)
This study aims to determine, 1) The effect of learning facilities on the learning independence of class VII students of SMP Negeri 2 Kotabaru; 2) The influence of learning motivation on the learning independence of seventh grade students of SMP Negeri 2 Kotabaru; 3) The effect of learning facilities and learning motivation together on the learning independence of class VII students of SMP Negeri 2 Kotabaru. This type of research is an ex post facto research using a descriptive quantitative approach. Using simple random sampling technique, class VII C and VII E were obtained as samples in this study. Data collection techniques using questionnaires or questionnaires. The data analysis technique used in this research is normality test and multicollinearity test. Meanwhile, to test the hypothesis using simple and multiple regression analysis or using t test and F test. The results of this study indicate that 1) there is an influence between learning facilities on learning independence. This is evidenced by the value of tcount greater than ttable (2.135 > 2.0322) and a significance value of 0.040, which means less than the predetermined significance level of 0 0.05 (0.040 < 0.05); 2) there is no influence of learning motivation on learning independence, because the tcount value is less than the ttable value (0.136 < 2.0322) and the significance value is 0.754, which means it is greater than the predetermined significance level of 0.05 (0.754 > 0, 05); 3) The results of multiple regression after the F test were obtained that the Fcount value was less than Ftable (2.595 < 3.27) and the significance value was obtained at 0.089 which means it is greater than the predetermined significance level of 0.05 (0.089 > 0.05). Based on these results, there is no influence between learning facilities and learning motivation on independent learning together in class VII students of SMP Negeri 2 Kotabaru. The magnitude of the coefficient of determination (R square) is 0.132 or 13.2%.